Sex differences in one-year recurrence and all-cause mortality following catheter ablation of ventricular tachycardia in structural heart disease - Tóth, Patrik; Komlósi, Ferenc; Vámosi, Péter; Arnóth, Bence; Szegedi, Nándor; Salló, Zoltán; Piros, Katalin; Perge, Péter; Osztheimer, István; Ábrahám, Pál; Széplaki, Gábor; Merkely, Béla; et al. (Frontiers in Cardiovascular Medicine, 2022)
We aimed to establish sex-specific predictors for 1-year VT recurrence and 1-year all-cause mortality in patients with structural heart disease undergoing catheter ablation. We analyzed data of 299 patients recorded in our structured registry. These included medical history, echocardiography parameters, laboratory results, VT properties, procedural data. Out of the 299 patients, 34 (11%) were female. No significant difference was found between women and men in terms of VT recurrence (p=0.74) or mortality (p=0.07). In females, severe mitral regurgitation (MR), tricuspid regurgitation (TR), presentation with incessant VT, and preprocedural electrical storm (ES) were associated with increased risk of VT recurrence. Diabetes, implanted CRT, VT with hemodynamic instability, ES and advanced MR were the risk factors of mortality in women. ACEi/ARB use predicted a favorable outcome in both endpoints among females. In men, independent predictors of VT recurrence were the composite parameter of ES and multiple ICD therapies, presentation with incessant VT, severe MR, while independent predictors of mortality were age, LVEF, creatinine and previously implanted CRT. According to our investigation, there are pronounced sex differences in predictors of recurrence and mortality following VT ablation.